20.9k views
2 votes
Find the solutions to y = (x – 1)2 for x = –3, 0, and 3.

(–3, –16), (0, 1), (3, 4)

(–3, 16), (0, 1), (3, 4)

(–3, –2), (0, 1), (3, 4)

(–3, –4), (0, –1), (3, 2)

User Kscott
by
5.6k points

1 Answer

0 votes

Answer:

if the 2 is the power of (x-1) here is ur answer


y = (x - 1 ){}^(2) \\if \: x \: is \: \: equal \: to \: - 3 \\ y =( - 3 - 1) {}^(2) \\ y = ( - 4) {}^(2) \\ y = 16


if \: x = 0 \\ y = (0 - 1) {}^(2) \\y = ( - 1) { }^(2) \\ y = 1


if \: x = 3 \\ y = (3 - 1) {}^(2) \\ y = 2 { }^(2) \\ y = 4

(-3,16) (0,1) (3,4)

User Pablo Venturino
by
5.4k points